A preliminary assessment of geological CO2 storage in the Khorat Plateau, Thailand - Chenrai, Piyaphong; Jitmahantakul, Sukonmeth; Bissen, Raphael; Assawincharoenkij, Thitiphan (Frontiers in Energy Research, 2022)
The main Carbon dioxide (CO2) emission in Thailand comes from the energy sector. Gas-based power plants including natural gas and biogas are considered as CO2 point sources and are mostly located in the Khorat Plateau. Geological CO2 storage is an important key element to reduce CO2 emissions from the CO2 point sources. The study is a preliminary assessment of a geological CO2 storage potential in the onshore Khorat Plateau. A potential geological formation is screened and ranked in terms of its suitability for a CO2 storage site (storage optimization, risk minimization and feasibility). The results of the screening and ranking indicate that the Khorat Permian carbonate is the most suitable for a geological CO2 storage, followed by the Khorat Group sandstone and Khorat evaporite. The Khorat Cenozoic basalts are not suitable for a geological CO2 storage in the Khorat Plateau. The results from this study should help to understand petroleum exploration and carbon capture and storage technology in Thailand, especially in Khorat area. However, it should be noted that more subsurface studies and more criteria should be included in the future to improve the reliability of the assessment of the geological CO2 storage in the Khorat Plateau.